Business Diagnostic Model: Case “Fábrica de café y chocolate El Agrario” San Vicente de Chucurí, Santander - Medina Cruz, Javier; Quintana Fuentes, Lucas Fernando; Olaya Cruz, Martha Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This work sought to support industrial micro-businesses in the cocoa sector, which lacked administrative and production process management tools. Consequently, the objective of the research was to develop a diagnostic model for organizational and productive transformation of MSMEs based on methodologies to carry out diagnoses, characteristics and structures, as inputs for generating an initial version of the model. For this, models adjusted to the reality of MSMEs in the food sector were identified and common variables among them were consolidated to generate attributes. In this regard, the theoretical model was designed based on a management approach, adjusted to the reality of the environment. For this achievement, a work plan was established that involved business visits for presentation and feedback of the model, collecting useful information to adjust and consolidate the data model. With this input, and identifying requirements to define transformation routes, based on self-evaluation and controlled planning, an application for organizational diagnosis and intervention for organizational transformation was built. The information was tabulated using self-diagnosis software for the administration and organizational quality of food producing MSMEs. (MQO v1.0-UNAD). This web application, developed by the authors, was considered for its design with a quantitative research approach and was applied and validated obtaining relevant results to know the state of support, missionary and strategic macro-processes which generate action plans to improve management indicators.